Livelihood status of women workers in shrimp sector at south western region in Bangladesh (Research in Agriculture Livestock and Fisheries, 2018)
In Bangladesh, women are engaging in shrimp sector to support themselves and their family as well. Current study was designed to study the socio-economic and hygienic status of the women working in shrimp sector (employee) in South Western region in Bangladesh (N=150). The study also selected women who are not working in shrimp sector (non-employee) in the same community (N=75) to evaluate impacts of shrimp industry on women. In socio-economic background analysis of the women, medium household size (46% and 65.3%), primary education level (63.3% and 48%), married (79.3% and 97.3%), drinking tube-well water (93.3 % and 92%) and polli electric facility (77.3% and 84%) was dominant in both cases. Average monthly household income and expenditure was found better among the employees (9235 ± 4042 Tk and 765 5± 3032 Tk, respectively) than the non-employees (9068 ± 3113 Tk and 7208 ± 2147 Tk, respectively). In summary, the study observed and suggesting that life style and hygienic condition is better among the women engaged in shrimp sector than the nonemployee in the same community.Res. Agric., Livest. Fish.5(3): 391-397, December 2018